Caminhos para driblar o desemprego : o caso da Inclusão Produtiva em Vitória/ES - Lima, Renata Santiago (2013)
The Productive Inclusion is a program that has as its legal basis the Social Assistance Law (LOAS) and certified by the National Social Assistance (PNAS) in order to meet the workers unemployed, stimulating the creation of jobs and income so that they can support themselves from their own work. This research aims to analyze the possibilities and limits of Inclusion Program for Productive to add in users of Social Policy in Vitoria s - ES city the labor market. Highlights that unemployment is not a fault with the system, but it is something functional to the capitalist mode of production. Discusses the concept of "social exclusion", which considers that the subjects are not out, but are within an unequal system that does not absorb inside the dynamics all employees availables, where the access to services is insufficient to ensure decent living standards for workers who are part of the Industrial Reserve Army. Presents the objectives, the legal framework, the public priority and action strategies with analysis of Productive Inclusion of experience in the Department of Social Services of the municipality of Vitória-ES during the period 2009-2011. Appreciates the dialectical method, the literature review and documentary research as guides to illuminate the analysis. Demonstrates that the limits of the program, from an analysis of the totality, not combat unemployment, giving rise to a dribble, a detour and establishing itself as the initiatives palliatives not salaried. At the same time, with the possibilities, it becomes an alternative relief of the poor living conditions, allowing gains subjective and objective of improving the standard of living, confidence, self-esteem and decision-making for workers in situations unemployment PNAS served by the municipality of Vitoria-ES.